Review of the genus Haloschizopera (Harpacticoida: Miraciidae, Diosaccinae) with description of a new species - Liu, Qinghe; Ma, Lin; Li, Xinzheng (Zootaxa, 2021)
Haloschizopera cheni sp. n., was recognized from our latest collections from the East China Sea. The new species is similar to H. abyssi Becher, 1974 but differs from it by the following combined features: baseoendopodal lobe of female P5 with five setae, P2 and P3 enp-3 both longer than enp-1-2 combined, and caudal rami longer than broad. Comparison of all the known species of Haloschizopera was performed. Species in the genus can be divided into four groups by the setal formulae of P3 and P4. The main diagnostic characters of each species are listed and a key to all known species of Haloschizopera is also provided.